2016
DOI: 10.1016/j.envint.2016.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Green spaces and General Health: Roles of mental health status, social support, and physical activity

Abstract: Green spaces are associated with improved health, but little is known about mechanisms underlying such association. We aimed to assess the association between greenness exposure and subjective general health (SGH) and to evaluate mental health status, social support, and physical activity as mediators of this association. This cross-sectional study was based on a population-based sample of 3461 adults residing in Barcelona, Spain (2011). We characterized outcome and mediators using the Health Survey of Barcelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
321
3
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 465 publications
(355 citation statements)
references
References 30 publications
18
321
3
13
Order By: Relevance
“…These include subjective perception of greenness [21] or selfreports of visiting green space [37], access to public green spaces such as parks as well as objective measures of surrounding greenness at residence, such as the NDVI applied in our study. Nevertheless, other studies that used objective measures of greenness as exposure variable and self-rated health as an outcome show results that point in the same direction as ours [20,38,39].…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…These include subjective perception of greenness [21] or selfreports of visiting green space [37], access to public green spaces such as parks as well as objective measures of surrounding greenness at residence, such as the NDVI applied in our study. Nevertheless, other studies that used objective measures of greenness as exposure variable and self-rated health as an outcome show results that point in the same direction as ours [20,38,39].…”
Section: Discussionsupporting
confidence: 54%
“…The role of social contacts in the association between greenness and health has been investigated in a previous study [19] which found that loneliness and perceived shortage of social support partially mediated the relation between green space and health. Another study came up with the same result [20] and Sugiyama et al similarly concluded that social coherence may contribute to the relationship between greenness and mental health, but found no empirical evidence for such an association for physical health [21].…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…Los espacios verdes urbanos, especialmente los ocupados por árboles, aportan importantes beneficios a los habitantes de las ciudades (Nowak et al 2007, Hartig et al 2011, Dadvand et al 2016, Carrus et al 2017, Vaz et al 2017, pero también algunos inconvenientes (Von Döhren & Haase 2015, Cariñanos et al 2017a, Vaz et al 2017, entre los que queremos destacar los problemas de salud ocasionados por la alergia al polen (Thompson & Thompson 2003, Cariñanos et al 2011. Esta situación suscita cada vez más interés, ya que las particularidades del entorno urbano, especialmente la contaminación, hace que los efectos sobre la población sean más notables (Majd et al 2004, Heinrich & Wichmann 2004, Sénéchal et al 2015 incluso cuando las concentraciones polí-nicas sean menores que en entornos rurales (Nicolau et al 2005).…”
Section: Introductionunclassified